Smart Auto Roll Sejadah ‘Prayer Mat’ / Mohd Amirul Akmal Mohd Fadzil - Mohd Fadzil, Mohd Amirul Akmal (2020)
Smart Auto Roll Sejadah needs to be highlighted in the necessities of worship around the world especially among muslims. This is because I had done some research and there are few problems that people have when they perform their prayer. One of the problems is people that use sejadah ,they will not roll it back and just leave it on the floor. Because of that, the prayer mat will easily get dirty and need to be cleaned up. The main idea or the main function of my product is, this prayer mat can roll in and out to use it before and after we perform our prayer. Another function is my prayer mat has a sensor that can correct our foot position. My company target population for sure muslim in Malaysia . There are some channels that my company uses to promote this product. For example like online shops and my own retail. For online shops there are Instagram, Facebook, Twitter and my own web which is SmartAutoRole.com . Customers can get info and buy my product there.